Reconstruction of Corruption Law Enforcement in the Anti Rasuah Institution "Corruption Eradication Commission (KPK)” (Based on Approach “Berani Jujur Pecat” (Dare Honest Fired)” - Adi Mansar (Randwick International of Social Science Journal, 2021)
Changes to the law are a necessity in accordance with the development of society, whether one law is revised or in the form of reconstruction or deconstruction by changing all existing laws, especially in one state institution that has a special function, for example the Corruption Eradication Commission (KPK) must follow development? What is the Institutional and Personal Position of the KPK after the status transfer to State Civil Apparatus? How effective is the KPK in eradicating corruption after it has been reconstructed? The reconstruction of the KPK institution is expected to bring the KPK to be better, more optimal and remain a supervisory institution for other law enforcement agencies that are able to bring order and legal certainty and justice to the people of Indonesia. The change in the status of KPK employees to State Civil Apparatus is a form of generalizing KPK personnel without making distinctions like so far, so it is feared that there will be no more competition and contestation between the investigative teams who work professionally. The existence of the KPK institution is re-examined with the enactment of Law Number 19 of 2019 concerning the KPK, hopefully the stigma of the superbody institution will remain attached to the KPK will not turn into a super executive institution that works at the request of certain parties and hopefully the KPK will maintain the psychology of the people who hope that the KPK must continue to exist even if fired for doing "HONEST" and the truth.